Pieczęć jako "forma symboliczna" - Perkun, Vitaliy (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The present article is an attempt to look at a seal in the broadest possible context of humanities, with an aim of finding novel fields and paths of research. The author discusses several directions of exploration of a seal – linguistic, anthropological, semiotic, and sociological; utilizing methods and results of research of art history and history of cognitive history, he present seal, regarded as a “symbolic form”, not only as a carrier, but also a memorial
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne